The Moderating Role of Islamic Financing Access in the Impact of Islamic Financial Knowledge and Financial Confidence on Financial Well-being among MSME Owners - Febriyanto, Febriyanto; Pariyanti, Eka; Japlani, Ardiansyah; Rinnanik, Rinnanik (Universitas Muhammadiyah Yogyakarta, 2024)
Research aims: This study aims to explore the relationship between Islamic financial knowledge, financial confidence, and financial well-being, with access to Islamic financing as a moderating variable, specifically targeting MSME owners in Lampung Province, Indonesia.Design/Methodology/Approach: Data was collected from MSME owners through surveys in Lampung Province, Indonesia. The study employed Jeffreys's Amazing Statistics Program (JASP) for data analysis, examining correlations between variables and assessing moderation effects.Research findings: The findings reveal positive correlations between Islamic financial knowledge, financial confidence, and financial well-being among MSME owners in Lampung Province, Indonesia. Additionally, access to Islamic financing was found to positively moderate the relationship between Islamic financial knowledge, financial confidence, and financial well-being.Theoretical Contribution/Originality: This research contributes to the existing literature by filling a gap and offering fresh insights into the factors influencing financial well-being among MSME owners, particularly within the context of Islamic finance. By uncovering the mechanisms underlying financial well-being in this demographic, it advances knowledge in the field.Practitioners/Policy Implications: Practitioners can develop targeted financial literacy programs and innovative financing products for MSME owners. Policymakers can streamline regulations and incentivize financial institutions to expand Islamic financing options, promoting financial inclusion and sustainable MSME growth in Lampung Province and beyond.Research Limitations/Implications: Despite its contributions, this study has limitations that should be acknowledged. The findings are based on data collected from MSME owners in Lampung Province, Indonesia, which may limit the generalizability of the results. Future research could expand the sample size and geographical scope to enhance the external validity of the findings.